Evaluation of Eurovision Song Contest as a Cultural Impact Tool: Kültürel Bir Etki Aracı Olarak Eurovision Şarkı Yarışması Üzerine Bir Değerlendirme - Bekcan, Umut; Uz Hançarlı, Pınar (Journal of History Culture and Art Research, 2021)
In this study, three claims/arguments regarding the emergence and function of the Eurovision Song Contest were put forward and tried to be grounded. First, the contest emerged as a tool for Western Europe to influence Eastern Europe culturally in the Cold War but it didn’t become an ideological conflict area of East-West. Second, the contest functioned as a stage of expressing the political problems/situations that countries experience within themselves or with each other in the Cold War era and aftermath. Third, although Turkey took place in the Western Europe side in the Cold War, this contest made Turkey feel non-European while having a different identity. In this context, the subject is discussed from the historical perspective with the assumption that the subject of history is unique. The study focused primarily on the concept of the Cold War and the contest. Then, it was explained with the examples which political problems/situations different from the Cold War ideological conflict environment were brought up on the contest platform. Finally, it was emphasized that the contest contributed to “us vs them” dichotomy in Turkey against Europe, contrary to Eurovision’s aim to form/create a common European culture.